P-122 Enabling patients to self-manage their pain; a pilot of a modified pain management programme. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Popert, Sheila; Csikos, Agnes; Moore, Peter; Cutler, Chris; Allsopp, Alison; Hill, Martin; Chand, Sonia; Brown, Sandra
Abstract : Background: Despite WHO recommendations for the management of pain the prevalence in palliative patients remains between 62–86% and management remains primarily pharmacological. There is good evidence for the efficacy of Pain Management Programmes (PMP) based on cognitive behavioural principles for patients with chronic pain. They have been shown to improve pain experience, mood, coping, and activity levels. Palliative patients are rarely eligible for inclusion on such programmes. Aim: To pilot and evaluate a holistic PMP tailored to the needs of palliative patients To reduce use of analgesics To introduce techniques for self-management of pain. Design: Patients with a life-limiting illness, complex pain, a Pain Score greater than 5 and a Karnofsky Performance Scale greater than 50% were eligible for enrolment in the six week programme Patients were initially assessed by a palliative consultant and a pharmacist to optimise drug regimens The PMP used a multi-disciplinary rehabilitative approach introducing the Pain Toolkit, Mindfulness, Relaxation, Cognitive Behavioural Techniques and Seated Exercise Evaluation was by structured questionnaires, the Hospital Anxiety and Depression Scale (HADS) and Pain Scores. Results: 18 patients met the inclusion criteria, nine patients agreed to take part, five patients completed the programme. Age range 32 to 74 years Patients reported moderate to severe anxiety and depression at the start. HADS scoring showed category improvement by the end Mindfulness and relaxation were rated as the most beneficial elements Patients reported group working supportive Pain scores did not change significantly but patients used less breakthrough medication Patients were able to employ techniques to self-manage pain. Conclusion: It can be difficult for palliative patients to attend a six- week programme; however for those who are well enough the pilot showed benefit, it improves pain self-management and reduces use of analgesics. Wider introduction of modified PMPs could be considered for palliative patients.